Minimizing Work Costs and Employee Performance: A Case Study at CV. Abadi Jaya in Bandar Lampung - Yamin, Yuliana; Safitri, Meilinda (Institut Ilmu Sosial dan Manajemen STIAMI, 2022)
Business competition is getting fiercer, both in the domestic (national) and traditional (global) markets. This study aimed to determine the relationship between minimizing work costs and employee performance at CV. Abadi Jaya in Bandar Lampung. The objects of this research were forty employees at CV. Abadi Jaya in Bandar Lampung. The researchers employed the descriptive-quantitative method. Furthermore, the researchers collected the research data through observation, interviews, questionnaires, and literature study. This study found that Ha was accepted, which indicated a relationship between the variable of minimizing work costs and employee performance. Therefore, the minimizing work costs variable was related to the employee performance variable. Also, the minimization of work costs was constant by one point, resulting in employee performance increased by 0.154%.